Study on Homocysteinemia as a Risk Factor of Ischemic Stroke - Pramanik, Md Amjad Hossain; Mallick, Achinta Kumar; Sarkar, Mukul Kumar; Haque, SM Emdadul; Kabir, Md Raseul; Tabassum, Muhatarima (TAJ: Journal of Teachers Association, 2021)
Despite recent advances, only two-third of all strokes can be attributed to known causal risk factors. Homocysteine (tHcy), a sulfur-containing amino acid, is now considered to be an important risk factor for vascular diseases, along with the established risk factors like hyperlipidemia, hypertension, diabetes mellitus, and smoking. Elevated homocysteine levels play a causal role in the pathogenesis of atherosclerosis, thromboembolism and vascular endothelial dysfunction with an increased incidence of ischemic stroke. This study aimed to find out the association of hyperhomocysteinemia with ischemic stroke. A total of 100 subjects were included in this study, 50 were ischemic stroke patients enrolled as case, and 50 were normal healthy individuals enrolled as control. Serum homocysteine level was measured in both case and control groups. The comparison was made in both groups regarding other common risk factors like diabetes mellitus, hypertension, smoking, dyslipidemia, family history, etc. Among 100 patients, 50 had ischemic stroke and 50 were healthy individuals. In this study, out of all patients, abnormal serum homocysteine level was found in 32% of cases and 12% of controls. The mean (±SD) serum homocysteine level was found 16.50±13.86 μmole/L in cases and 9.46±3.49 μmole /L in the control group. Significant (p<0.05) difference was found between the case and the control. The incidence of hyperhomocysteinemia is higher in ischemic stroke cases than that in age-sex-matched healthy controls. In our study, serum homocysteine was high in both younger age group patients (16.65±14.55 μmole/L vs. 9.52±3.19 μmole/L) and older age group patients (16.33±9.87 vs. 9.35±3.97 μmole/L,) in case and control group respectively. Significant (p<0.05) difference was found between the case and the control. Multiple logistic regression analysis showed that abnormal serum homocysteine is an independent risk factor of ischemic stroke. So we conclude that hyperhomocysteinemia is an important and independent risk factor for the development of ischemic stroke. Hypertension and smoking are important contributory to elevated serum homocysteine. TAJ 2021; 34: No-1: 33-39